WTO and other international aspects of ACP-EU fisheries relations: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
WTO rules applying to international fish trade and treaties, as well as conventions governing fisheries management and conservation, are of considerable importance for ACP fish-producing countries. This Executive Brief presents the main international developments in the fisheries sector in 2012-13, focusing on the main implications for ACP-EU trade relations. This includes the discussions on fisheries subsidies, the implementation of the IUU Fishing Regulation, and, more broadly, how EU policies affect WTO negotiations on fisheries.